A mixed method approach to analysing patterns and drivers of antibiotic use and resistance in beef farms in Argentina - Bedford, Cherrill; Galotta, Maria Laura; Oikonomou, Georgios; de Yaniz, Guadalupe; Nardello, Matías; Sánchez Bruni, Sergio; Davies, Peers (Frontiers in Veterinary Science, 2024)
IntroductionAntimicrobial resistance is a challenge to be faced by all livestock sectors; within beef farming, antibiotic use patterns vary by country and management practices. Argentina is a country with high beef production & consumption but limited information surrounding antibiotic use. The aims of this project was to understand how antibiotics are being used across the beef industry in Argentina and exploring drivers of usage.MethodsQuantitative and qualitative data was collected by: A survey of breeding and feedlot farms including antibiotic use (from purchase data); a detailed analysis of two feedlot farms’ therapeutic antibiotic use records; a survey of vets’ views on certain antibiotic practices; and a focus group of farmers and vets focusing on wider influences affecting decision making. Antibiotic use data was calculated using mg/population corrected unit (PCU) (ESVAC) and thematic analysis was used to identify drivers of antibiotic use among participants.ResultsThe median use across 17 farms that supplied purchase data was 76.52  mg/kg PCU (ESVAC; IQR  =  36.81  mg/kg PCU [ESVAC]). The detailed farm records showed that the largest reason for treatment was group treatments (72.92% of treatments) followed by treatment for respiratory disease (12.75% of treatments). Macrolides accounted for 76.37% of treatments. Nearly half of farms used routine prophylactic treatment for arriving animals (n  =  7/18). The use of quarantine and ‘sick pens’ were seen as important by surveyed vets with antibiotic prophylaxis and in-feed antibiotics seen as contributors to antibiotic resistance. The focus group highlighted the influence of the economic and political landscape on husbandry practices and the responsibility the farming sector had towards antibiotic stewardship.DiscussionOverall, Argentine beef feedlots resemble North American beef feedlots in terms of antibiotic practices but with considerably lower usage, with in-feed monensin representing a large proportion of total ABU. The adaptation period presents a challenge to animal health; antibiotics are administered a prophylaxis, metaphylactic and individual treatments depending on farm management practices. Further research into internationally comparable measures of ABU and detailed cost-benefit analysis of practical, on-farm interventions are needed to aid improved antimicrobial stewardship in livestock systems globally.